Causes of albuminocytological dissociation and the impact of age-adjusted cerebrospinal fluid protein reference intervals: a retrospective chart review of 2627 samples collected at tertiary care centre. Issue 2 (13th February 2019) - Brooks, John Alexander; McCudden, Christopher; Breiner, Ari; Bourque, Pierre R
Abstract : Objective: We set out to test the discriminative power of an age-adjusted upper reference limit for cerebrospinal fluid total protein (CSF-TP) in identifying clinically relevant causes of albuminocytological dissociation (ACD). Methods: We reviewed the charts of 2627 patients who underwent a lumbar puncture at a tertiary care centre over a 20-year period. Samples with CSF-TP above 45 mg/dL (0.45 g/L) were included. Samples with white cell count >5×10 9 /L, red cell count >50×10 9 /L and glucose <2.5 mmol/L (45 mg/dL) were excluded as were samples with incomplete data and those taken from paediatric patients (ie, age <18 years old). Patients with CSF-TP elevated above 45 mg/dL were considered to have 'pseudo' ACD unless their CSF-TP was in excess of age-adjusted norms in which case they were considered to have 'true' ACD. Adjustment for sex was not applied to the age-adjusted norms although the importance of gender has been previously described. Results: The presence of ACD was associated with a broad range of neurological diagnoses. Among all 2627 patients with ACD, a clinical diagnosis explaining CSF-TP elevation was identified in 57% of cases. 'True' ACD was associated with a suitable diagnosis in 75% of cases, whereas patients with 'pseudo' ACD showed an appropriate diagnosis in only 51% of cases. Use of an age-adjusted upper reference limit favoured the detection of polyneuropathy patients (13.5% proportionate increase) and excluded a larger number of patients with isolated headache (10.7% proportionate decrease; p<0.0001). Conclusions: Elevated CSF-TP is a common finding, with a range of underlying causes. Use of an age-adjusted upper reference limit for the CSF-TP value improves diagnostic specificity and helps to avoid overdiagnosis of ACD.